Long‐Lived Second Near‐Infrared Luminescent Probes: An Emerging Role in Time‐Resolved Luminescence Bioimaging and Biosensing. Issue 2 (15th November 2022) - Feng, Ruibing; Li, Guodong; Ko, Chung-Nga; Zhang, Zhang; Wan, Jian-Bo; Zhang, Qing-Wen
Abstract : Luminescence bioimaging and biosensing in the second near‐infrared (NIR‐II) spectral window (1, 000–1, 700 nm wavelengths) is a newly emerging technique that is extensively used in fundamental research and clinical practice. Owing to its advantages, including deep tissue penetration and excellent temporal resolution, this technique has shown tremendous promise for target‐specific imaging and noninvasive monitoring. However, developing bioimaging modalities that enable target‐specific imaging with high resolution and sensitivity remains a great challenge today. Compared with NIR‐II fluorescence imaging, NIR‐II luminescence lifetime imaging with advantages such as lower background noises, higher sensitivity, and higher spatial resolution has opened up new avenues for deep tissue imaging and biomedical applications. Herein, various types of long‐lived NIR‐II luminescent probes, including complex dyes, rare‐earth‐doped nanoparticles, organic compound‐loaded nanoparticles, inorganic‐based dots and nanotubes, as well as the main types of time‐resolved luminescence techniques including time‐domain (e.g., time‐correlated single‐photon counting, time‐gated detection, pulse sampling, etc.) and frequency‐domain systems are first summarized. The unique advantages of long‐lived NIR‐II luminescent probes and their critical roles in bioimaging and biosensing are also highlighted. Finally, the present challenges and future directions of long‐lived NIR‐II luminescent probes in biomedical research, translational research, and (pre‐)clinical studies are discussed. Abstract : This review describes primary roles of long‐lived second near‐infrared (NIR‐II) luminescent probes in time‐resolved luminescent bioimaging and biosensing applications, including in vivo tumor bioimaging, in vivo HILI bioimaging, pH sensing, diet metabolism and biodistribution monitoring, thermosensing, and in vivo information storage, as well as discusses future directions of novel long‐lived NIR‐II luminescent probes in biomedical research, translational research, and clinical studies.